A Comparison of the Red Cell Uptake of 131I-T3 and 125I-T3 as a Test of Thyroid Function - Bell, T. K.; Todd, S. J. (Nuklearmedizin - NuclearMedicine, 1967)
Investigation of the in vitro red cell uptake of triiodothyronine as a test of thyroid function showed that there was no significant difference when fresh saline dilutions of 125I-T3 were used in place of 131I-T3.